Safety assessment of the prophylactic use of silicone gel sheets (Lady Care®) for the prevention of hypertrophic scars following caesarean section. (3rd April 2021) - Ito, Yuki; Konishi, Akiko; Okubo, Miki; Sato, Takuma; Hasegawa, Akihiro; Yabuzaki, Keiko; Matsuoka, Tomona; Yamamura, Michihiro; Inoue, Momoko; Udagawa, Haruhiko; Kajiwara, Kazuhiro; Kamide, Taizan; et al.
Abstract: This study aimed to investigate the side effects of silicone gel sheet (Lady Care ® ) and evaluate its prophylactic efficacy in preventing abnormal scarring. Sixty women who underwent caesarean section were recruited from September 2016 to September 2017 in this prospective study. Lady Care ® was applied from the 2nd to the 6th postoperative months. Side effects of Lady Care ® were evaluated through medical examinations and questionnaires. A plastic surgeon diagnosed abnormal scarring. Pruritus was diagnosed in 25 (47.2%) patients; folliculitis, four (7.5%); dry skin, four (7.5%); contact dermatitis, three (5.7%); wound infection, two (3.8%); and epidermolysis, one (1.9%), albeit with mild severity. Following Lady Care ® application, no abnormal scarring and mild hypertrophic scarring was observed in 32 (64.0%) and 18 (36.0%) patients respectively. Of seven patients with pre-existing hypertrophic scars, only two showed hypertrophic scarring after Lady Care ® application. Our findings support the safety and prophylactic efficacy of Lady Care ® . Impact Statement: What is already known on this subject? The incidence of abnormal scarring, i.e. keloid or hypertrophic scar formation after caesarean section (CS) is reported to be ∼41%. Abnormal or excessive scar formation can lead to functional limitations, pruritus, pain and cosmetic issues. Studies have also shown a prophylactic effect of the application of silicone materials against the development of hypertrophic and keloid scars, though prohibitive cost and lack of adhesiveness of such gel sheets are known factors limiting their usage. What the results of this study add? The new silicone gel sheet 'Lady Care ® ' has strong adhesive properties and is consequently not easily peeled off. Furthermore, it is easy to use and economically efficient. What the implications are of these findings for clinical practice and/or further research? This is the first clinical trial on the application of Lady Care ® silicone gel sheet for the prevention of CS scarring. Our findings support the safety and prophylactic efficacy of Lady Care ® .